Lactobacillus fermentum B153 from human colostrum modulates intestinal immunity and gut microbiota in obese mice model - Juqing Huang; Xiaohui Cai; Xiaoyan Liu; Gongti Lai; Xuefang Guan; Bingyan Chen; Qi Wang (Journal of Functional Foods)
This study evaluated the effects of L. fermentum B153 (derived from human colostrum) on intestinal immunity and gut microbiota in a high-fat diet-induced obese mouse model. The results indicate that treatment with L. fermentum B153 significantly decreased the perirenal adipose index and increased the villus height to crypt depth (V/C) ratio in both the ileum and jejunum of obese mice. Intestinal inflammation induced by the high-fat diet was alleviated by L. fermentum B153, as evidenced by the upregulation of E-cadherin and IL-6 mRNA expression, alongside the downregulation of TNF-α mRNA expression. Furthermore, L. fermentum B153 significantly altered the gut microbiome composition of obese mice, characterized by a substantial increase in the relative abundance of the potentially beneficial genus Akkermansia and a notable decrease in the richness of potentially harmful bacteria (e.g., Lachnoclostridium, Romboutsia and Dubosiella). In conclusion, L. fermentum B153 positively modulated intestinal immunity and gut microbiota in obese mice.